LA ROUMANIE AU BOUT DE LA TRANSITION DÉMOGRAPHIQUE: DISPARITÉS ET CONVERGENCES RÉGIONALES - IONEL MUNTELE (Revue Roumaine de Géographie)
The analyses of some long series of demographic data, got by processing various and often contradictory recordings, clearlypoint out the distinct stages of the Romanian society’s adjustment to the classical pattern of the demographic transition. The presence of a diffusion of this pattern was confirmed both at the national and regional level, starting from several nuclei earlier connected to the modernization process (the capital city of the country, theSouth of Transylvania and Banat), well known from the literature dealing with this topic. Moreover, there have been permanent changes in the spatial distribution of the main demographic indicators, having as principal consequence a continuous diminishing of the regional disparities, generally interpreted by means of the level of economic and social modernization. The present situation, at the end of a demographic transition which has been rather fast and which has faced numerous convulsions, requires a new analysis in keepingwith the most recent interpretations and points of view on the existence of a new demographic regime – the post transitional one (cf. van der Kaa, 1997). At the regional level one can no longer speak of the classical opposition between the traditional behaviour characteristic to the North-East of the country and the modernbehaviour typical of the West. The antithesis between the regions facing a typical post transitional regime (experiencing a rebalancing of the fertility indicators), partly adapted to the pattern of the developed countries (mainly the capital) and the regions that are passing through the last stage of the classical transition (certain counties in the North-East of the country) is of present interest. These analyses prove the fact that Romaniahas got out of the paradigm of the imbalances that opposed the areas with labour force deficit to the areas with man power excess (triggering ample internal migratory flows), entering the paradigm of exhausting its own labour resources, just like most Western countries.